THE FUNCTION OF NOTARIES IN THE ESTABLISHMENT OF INDIVIDUAL COMPANIES POST JOB CREATION LAW - I Putu Adi Adnyana Putra; Putu Ayu Sriasih Wesna (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The aim of this research is to analyze the function of notaries in the establishment of individual companies after the Job Creation Law. The type of research used is normative legal research which focuses on primary, secondary and tertiary legal materials and uses a statutory and conceptual approach. The research results show that the notary does not have a function in making authentic deeds for the establishment of individual limited liability companies because the establishment of individual limited liability companies does not require an authentic deed and a statement of establishment that is registered electronically is sufficient. The notary will function when an individual company decides to change to a capital partnership where the notary can provide legal counseling and assess the validity of the documents. The establishment of an individual company is based on the provisions of PP No. 8 of 2021 by making a statement of establishment in Indonesian and registering it via the AHU Online portal. With the change in the function of notaries in making authentic deeds of company establishment, there are still concerns regarding the legal validity and security of the identity of founders, directors and shareholders during the electronic registration process. The government is advised to change the regulations by involving a notary to make authentic deeds and create new regulations that specifically contain provisions relating to individual limited companies.